Conflict Management in Culturally Diverse Workplaces : A lower-level manager’s perspective - Tran, Nhi (My University, 2022)
This study discusses the intercultural workplace conflict management from lower-level manager’s point of view. The main objective of this study is to better understand how managers can develop the intercultural conflict management skills. The sub-objectives are to analyse workplace conflicts in intercultural context, determine crucial intercultural managerial skills, and understand the role of the manager as an interpreter with supervisory duties. Studying the workplace conflicts through intercultural lenses is important to understand the causes of conflicts in culturally diverse settings. Identifying the crucial managerial skills for conflict management shows the areas that require more attention. Thus, understanding how intercultural conflicts are created help to analyse different conflict management strategies and explore manager’s role. The theoretical background of the study follows the structure of culture-based social ecological conflict model and includes additional literature and theories related to the components. The empirical research is conducted by qualitative interviews of informants who meet the criteria. The semi-structured interviews of five informants were collected and transcribed. For the analysis of the data, thematic analysis method was selected. The findings of this study indicate that conflicts occurring at culturally diverse workplaces were related to apparent functional differences, which makes cultural differences an enhancing factor rather than a cause of conflicts. The study supports that lower-level managers have an important role in intercultural conflict settings in intervening conflict situations through interpretation. Yet the managerial skills are rather underappreciated and require self-learning because of insufficient training for the position. What is expected from the manager differ between different actors. Thus, responsibilities of a manager are vaguely determined, and the task-effectiveness was found to be valued over relational-effectiveness. The role of the manager as an interpreter and intervener is changing with the experiences, which highlights the importance of learning in the field through trial and error.

Tässä tutkimuksessa käsitellään kulttuurienvälisten työpaikkakonfliktien hallintaa alemman tason johtajien näkökulmasta. Tutkimuksen päätavoitteena on ymmärtää paremmin, miten johtajat voivat kehittää kulttuurienvälisten konfliktien hallintataitoja. Alatavoitteina on analysoida työpaikkakonflikteja kulttuurienvälisessä kontekstissa, määrittää kulttuurienväliset johtamistaidot, jotka ovat ratkaisevia, ja ymmärtää johtajan rooli tulkkina, jolla on esimiestehtäviä. Työpaikkakonfliktien tutkiminen kulttuurienvälisen näkökulman kautta on tärkeää, jotta voidaan ymmärtää konfliktien syitä kulttuurisesti erilaisissa ympäristöissä. Konfliktinhallinnan kannalta ratkaisevien johtamistaitojen tunnistaminen osoittaa, mihin alueisiin on kiinnitettävä enemmän huomiota. Näin ollen kulttuurienvälisten konfliktien syntymisen ymmärtäminen auttaa analysoimaan erilaisia konfliktinhallintastrategioita ja tutkimaan johtajan roolia. Tutkimuksen teoreettinen tausta noudattaa kulttuuripohjaisen sosiaalis-ekologisen konfliktimallin rakennetta, ja siihen sisältyy osiin liittyvää lisäkirjallisuutta ja teorioita. Empiirinen tutkimus toteutetaan kriteerit täyttävien informanttien laadullisilla haastatteluilla. Viiden informantin puolistrukturoidut haastattelut kerättiin ja kirjoitettiin puhtaaksi. Aineiston analysointiin valittiin temaattinen analyysimenetelmä. Tutkimuksen tulokset osoittavat, että kulttuurisesti erilaisissa työpaikoissa esiintyvät konfliktit liittyivät ilmeisiin toiminnallisiin eroihin, mikä tekee kulttuurieroista pikemminkin konflikteja lisäävän tekijän kuin niiden syyn. Tutkimus tukee sitä, että alemman tason johtajilla on kulttuurienvälisissä konfliktiympäristöissä tärkeä rooli puuttua konfliktitilanteisiin tulkinnan kautta. Johtamistaitoja kuitenkin arvostetaan melko vähän, ja ne edellyttävät itseopiskelua, koska tehtävään ei ole riittävästi koulutusta. Se, mitä johtajalta odotetaan, vaihtelee eri toimijoiden välillä. Näin ollen johtajan vastuut ovat epämääräisesti määriteltyjä, ja tehtävän tehokkuus on arvotettu suhteelliseen tehokkuuteen nähden. Johtajan rooli tulkkina ja välittäjänä muuttuu kokemusten myötä, mikä korostaa kentällä kokeilujen ja erehdysten kautta tapahtuvan oppimisen merkitystä.
Keywords: Intercultural conflict, workplace conflict, conflict management, lower-level manager